2009
DOI: 10.1016/j.apal.2008.06.019
|View full text |Cite
|
Sign up to set email alerts
|

D-completions and thed-topology

Abstract: a b s t r a c tIn this article we give a general categorical construction via reflection functors for various completions of T 0 -spaces subordinate to sobrification, with a particular emphasis on what we call the D-completion, a type of directed completion introduced by Wyler [O. Wyler, Dedekind complete posets and Scott topologies, in: B. A key result is that all completions of a certain type are universal, hence unique (up to homeomorphism). We give a direct definition of the D-completion and develop its th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Domain theory plays a foundational role in denotational semantics of programming languages. In domain theory, the d-spaces, well-filtered spaces and sober spaces form three of the most important classes (see [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][28][29]). Let Top 0 be the category of all T 0 spaces and Sob the category of all sober spaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Domain theory plays a foundational role in denotational semantics of programming languages. In domain theory, the d-spaces, well-filtered spaces and sober spaces form three of the most important classes (see [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][28][29]). Let Top 0 be the category of all T 0 spaces and Sob the category of all sober spaces.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that Sob is reflective in Top 0 (see [6,9]). Using d-closures, Wyler [22] proved that Top d is reflective in Top 0 (see also [16,27]). Later, Ershov [5] showed that the d-completion of X (i.e., the d-reflection of X) can be obtained by adding the closure of directed sets onto X (and then repeating this process by transfinite induction).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Ershov [5] showed that the d-completion (i.e., the d-reflection) of X can be obtained by adding the closure of directed sets onto X (and then repeating this process by transfinite induction). In [18], using Wyler's method, Keimel and Lawson proved that for a full subcategory K of Top 0 containing Sob, if K has certain properties, then K is reflective in Top 0 . They showed that Top d and some other categories have such properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the category of all sober spaces and that of d-spaces are reflective in the category of all T 0 spaces (see [7,12,23]). Recently, following Ershov's method of constructing the d-completion of T 0 spaces, Shen, Xi, Xu and Zhao [22] presented a construction of the well-filtered reflection of T 0 spaces.…”
Section: Introductionmentioning
confidence: 99%